A time-calibrated phylogeny of the diversification of Holoadeninae frogs - Chaves, Júlio C. M.; Hepp, Fábio; Schrago, Carlos G.; Mello, Beatriz (Frontiers in Bioinformatics, 2024)
The phylogeny of the major lineages of Amphibia has received significant attention in recent years, although evolutionary relationships within families remain largely neglected. One such overlooked group is the subfamily Holoadeninae, comprising 73 species across nine genera and characterized by a disjunct geographical distribution. The lack of a fossil record for this subfamily hampers the formulation of a comprehensive evolutionary hypothesis for their diversification. Aiming to fill this gap, we inferred the phylogenetic relationships and divergence times for Holoadeninae using molecular data and calibration information derived from the fossil record of Neobatrachia. Our inferred phylogeny confirmed most genus-level associations, and molecular dating analysis placed the origin of Holoadeninae in the Eocene, with subsequent splits also occurring during this period. The climatic and geological events that occurred during the Oligocene-Miocene transition were crucial to the dynamic biogeographical history of the subfamily. However, the wide highest posterior density intervals in our divergence time estimates are primarily attributed to the absence of Holoadeninae fossil information and, secondarily, to the limited number of sampled nucleotide sites.